1997
DOI: 10.1159/000190274
|View full text |Cite
|
Sign up to set email alerts
|

Aminoglycoside-Associated Fanconi’s Syndrome: An Underrecognized Entity

Abstract: The Fanconi syndrome is an array of multiple proximal renal tubular dysfunctions occurring in association with several exogenous toxins, such as aminoglycosides. These antibiotics remain the drugs of choice in most gram-negative infections, but nephrotoxicity is the main drawback for them. Furthermore, the nephrotoxic effects may be overlooked with routine analyses. With the purpose of making physicians aware of this underrecognized complication, we are reporting here 3 cases of Fanconi’s syndrome related to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…In preterm infants, gentamicin administration appears to result in an increase in magnesium loss. Several tubular disorders with hypomagnesemia and other electrolyte disturbances have been reported in children and adults after long-term gentamicin administration [30,31,32]. Studies in rats have shown that gentamicin administration causes dose-related Mg and Ca renal wasting, days before any evidence of renal injury [33].…”
Section: Discussionmentioning
confidence: 99%
“…In preterm infants, gentamicin administration appears to result in an increase in magnesium loss. Several tubular disorders with hypomagnesemia and other electrolyte disturbances have been reported in children and adults after long-term gentamicin administration [30,31,32]. Studies in rats have shown that gentamicin administration causes dose-related Mg and Ca renal wasting, days before any evidence of renal injury [33].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the patient presented with renal glucosuria, phosphaturia, uricosuria, and metabolic hyperchloremic acidosis, features of a proximal tubular dysfunction. Even though the Fanconi syndrome has been associated with the administration of a number of antibiotics, an aminoglycoside-induced Fanconi syndrome is rare [2,[5][6][7][8]. Advanced age and longterm drug administration may predispose to the renal tubular damages observed [3,9,10,13,15].…”
Section: Discussionmentioning
confidence: 99%
“…The extent of the tubular dysfunction ranges from clinically undetectable enzymuria to substantial wasting of electrolytes and minerals [3]. Two types of renal tubular damage have been reported: a Fanconi-like syndrome of a rather generalized proximal tubular damage and a syndrome of hypokalemic metabolic alkalosis associated with hypomagnesemia [4][5][6][7][8][9][10][11][12][13][14][15][16]. We report 2 representative cases of a reversible tubular damage related to chronic aminoglycoside administration.…”
Section: Introductionmentioning
confidence: 99%
“…However, gentamicin may cause a dose-dependent nephrotoxicity (Bennett, 1997). Previous studies have shown that gentamicin is mainly concentrated in the proximal tubular cells, and the resultant renal dysfunction may be recognized as Fanconi-like syndrome of a proximal tubular damage (Pastoriza-Munoz et al, 1979;Gainza et al, 1997).…”
Section: Introductionmentioning
confidence: 99%